Unloading method in coordinated harvesting - Wang, Xiaoxiong; Man, Zhihong; Wang, Zhuo; Bai, Xiaoping; Wang, Jian; Ge, Zhikang (International Journal of Agricultural and Biological Engineering, 2025)
In this study, a novel unloading method was developed for the operation of the unloading spout during the loading process in a master-slave automatic harvesting system. It demonstrated that uniform and full loading in the grain tank can be achieved by uninterrupted unloading with the motion of the unloading spout. First, the overflow algorithm is proposed to divide the loading process into multiple loading rounds. In each round, a specific loading area and target loading height are assigned to achieve better uniformity. Subsequently, complete coverage path planning and transfer path planning algorithms are developed to guide the motion of the unloading spout during different loading rounds. With the motion of the unloading spout, loading can be carried out accurately to maximize the capacity utilization of the grain tank, which can reduce the round-trip frequency of the transport vehicle and improve the energy and time efficiency of the harvesting operation. Simulation results are provided to validate the excellent performance of the presented unloading method. Key words: coordinated harvesting; loading uniformity; overflow algorithm; path planningDOI: 10.25165/j.ijabe.20251802.8863Citation: Wang X X, Man Z H, Wang Z, Bai X P, Wang J, Ge Z K. Unloading method in coordinated harvesting. Int J Agric & Biol Eng, 2025; 18(2): 45–54.